Medical informatics : tutorial for foreign English-speaking students - Knigavko, Volodymyr; Zaytseva, Olga; Bondarenko, Maryna; Batyuk, Liliya; Rukin, Aleksey (My University, 2019)
The tutorial was created in accordance with the updated working curriculum of the discipline "Medical Informatics". The structure of the tutorial suggests the possibility of its use in practical classes in this discipline. The manual is adapted for foreign students of medical universities studying in English.
Approved by the Scientific Council of KhNMU. Protocol No 8 of 19.09.2019.
Keywords: coding; classification; standardization and algorithmization; visualization of biomedical data; medical images; biological signals; evidence-based medicine; medical hardware and software systems; nanotechnology; system analysis; healthcare system; medical research; physiological cybernetics; НП2019